Explaining variations in hospitals' use of strategic human resource management: How environmental and organizational factors matter. Issue 1 (January 2021) - Schneider, Annika M.; Oppel, Eva-Maria; Winter, Vera
Abstract : Background: Against the background of increasing workforce-related challenges such as staff shortages, strategic human resource management (SHRM) has gained importance in hospitals. Although the positive implications of SHRM for hospital performance are well known and commonly accepted in research and practice, hospitals still vary in its use. However, the sources of variations in hospitals' use of SHRM are largely unknown. Purpose: Various organizational and environmental factors were used in this study to explain the variations in hospitals' use of SHRM for physicians and nurses. Methodology: Data were obtained from a hospital survey ( n = 172) on topics related to human resource management in hospitals and linked to different secondary data sets. We apply multiple linear regression modeling to investigate the association between organizational and environmental characteristics and hospitals' use of SHRM for nurses and physicians. Findings: Our results suggest that organizational factors such as private for-profit and nonprofit ownership (compared to public ownership), academic teaching status, and the strategic involvement of the human resource administration are positively associated with hospitals' use of SHRM. None of the environmental factors investigated in this study was significantly related to hospitals' use of SHRM. Practical Implications: The study results increase our understanding of variations in hospitals' use of SHRM. Although organizational characteristics were found to explain variations in SHRM, environmental factors seem unrelated with hospitals' use of SHRM. Our results inform both hospital managers and policy makers about possible approaches to enhance SHRM use in hospitals. Furthermore, profound knowledge about factors associated with SHRM will help to enhance our understanding of anticipating changes in hospitals' use of SHRM through organizational- and environmental-oriented interventions.